Bibliometric Analysis From 2014-2024: Integration of Ethnoscience in Science Learning - Endah Febri Setiya Rini; Sentot Budi Rahardjo; Bramastia Bramastia (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: Ethnoscience has become a fairly well-established field among academics, although the topic is still developing. This study aims to analyze research trends related to ethnoscience published in the period 2014 to 2024. Methodology: This study uses bibliometric analysis and systematic literature review. Data collection was carried out by searching for the keyword "Ethnoscience" in October 2024. The data was sourced from the Scopus database and obtained 271 documents. 166 articles were obtained after filtering. Furthermore, analyzed using VOSviewer. Main Findings: The results showed that ethnoscience has increased significantly as a research topic from 2014 to 2021; ethnoscience in science learning is more widely studied in Indonesia. The author who researched the most ethnoscience is Sudarmin, with a total of 16 documents. This study also highlights the latest research approaching 2022–2024 and its impact on student skills. Novelty/Originality of this study: These findings also highlight the importance of ethnoscience in local and traditional studies and focus on the development of science and education.